Influence of bacterial N-acyl-homoserine lactones on growth parameters, pigments, antioxidative capacities and the xenobiotic phase II detoxification enzymes in barley and yam bean - Götz-Rösch, Christine; Sieper, Tina; Fekete, Agnes; Schmitt-Kopplin, Philippe; Hartmann, Anton; Schröder, Peter (Frontiers in Plant Science, 2015)
Bacteria are able to communicate with each other and sense their environment in a population density dependent mechanism known as quorum sensing (QS). N-acyl-homoserine lactones (AHLs) are the QS signalling compounds of Gram-negative bacteria which are frequent colonizers of rhizospheres. While cross-kingdom signalling and AHL-dependent gene expression in plants has been confirmed, the responses of enzyme activities in the eukaryotic host upon AHLs are unknown. Since AHL are thought to be used as so-called plant boosters or strengthening agents, which might change their resistance towards radiation and/or xenobiotic stress, we have examined the plants’ pigment status and their antioxidative and detoxifying capacities upon AHL treatment. Because the yield of a crop plant should not be negatively influenced, we have also checked for growth and root parameters. We investigated the influence of three different AHLs, namely N-hexanoyl- (C6-HSL), N-octanoyl- (C8-HSL) and N-decanoyl- homoserine lactone (C10-HSL) on two agricultural crop plants. The AHL-effects on Hordeum vulgare (L.) as an example of a monocotyledonous crop and on the tropical leguminous crop plant Pachyrhizus erosus (L) were compared. While plant growth and pigment contents in both plants showed only small responses to the applied AHLs, AHL treatment triggered tissue- and compound-specific changes in the activity of important detoxification enzymes. The activity of dehydroascorbate reductase (DHAR) in barley shoots after C10-HSL treatment for instance increased up to 384% of control plant levels, whereas superoxide dismutase (SOD) activity in barley roots was decreased down to 23% of control levels upon C6-HSL treatment. Other detoxification enzymes reacted similarly within this range, with interesting clusters of positive or negative answers towards AHL treatment. In general the changes on the enzyme level were more severe in barley than in yam bean which might be due to the different abilities of the p